Agonal Perspectives on Nietzsche's Philosophy of Critical Transvaluation - Siemens, Herman W. (Monographien und Texte zur Nietzsche-Forschung, 2021)
Nietzsche's concept of the agon or Wettkampf, a measured and productive form of conflict inspired by ancient Greek culture, has attracted a good deal of interest in Nietzsche studies and beyond. This book, by a leading expert on the topic, brings together research conducted over 20 years with a focus on the agon as a model or cypher for Nietzsche's philosophical practice and its implications for his project of critical transvaluation (Umwertung).